Quasi‐Parallel NiFe Layered Double Hydroxide Nanosheet Arrays for Large‐Current‐Density Oxygen Evolution Electrocatalysis - Ye, Qinglan; Li, Lingfeng; Li, Hangyang; Gu, Xiangyang; Han, Boming; Xu, Xuetang; Wang, Fan; Li, Bin (ChemSusChem, 2022)
Designing advanced electrocatalysts for oxygen evolution at large current density (>500 mA cm−2) is critical to practical water splitting applications. Herein, a novel quasi‐parallel NiFe layered double hydroxide (NiFe LDH) nanosheet arrays with pattern alignment on Ni foam was developed. The initial α‐Ni(OH)2 layer induced effective coprecipitation between Ni2+ and Fe3+ for the formation of LDH phase, guaranteeing the electronic pulling effect among metal cations and enhancing the interaction between active materials and substrate for excellent adhesion and electrical conductivity. Quasi‐parallel NiFe LDH nanoarrays exhibited outstanding oxygen evolution activity with a small Tafel slope of 30.1 mV dec−1 and overpotentials of 196, 255, and 284 mV at a current density of 10, 500, and 1000 mA cm−2 in 1.0 m KOH solution, respectively, and high stability over 40 h at 750 mA cm−2. This work presents a new strategy towards fabricating electrode materials with exceptional performance. Oxygen evolution: Quasi‐parallel NiFe layered double hydroxide nanosheet arrays with domain patterns are formed on Ni foam. Benefiting from the enhanced interaction between active materials and substrate, the electrode delivers high electrocatalytic activity for the oxygen evolution reaction (overpotentials of 196, 255, and 284 mV at 10, 500, and 1000 mA cm−2) and excellent long‐term stability.